Can official advice improve mortgage-holders' perceptions of switching? An experimental investigation - Shane Timmons; Martina Barjaková; Terence J. McElvaney; Pete Lunn (The Economic and Social Research Institute (ESRI), 2019)
Encouraging consumers to seek out and switch to lower-rate mortgages is important both for the individual consumer's finances and for functioning competitive markets, but switching rates are low. We conducted an experiment with mortgage-holders to test whether official advice on how to select good mortgage products and how to navigate the switching process alters perceptions of switching. The experiment shows that the advice made consumers more sensitive to interest rate decreases and more favourable towards switching at longer terms. It also increased consumers' confidence in their ability to select good offers. The findings imply that advice from policymakers can change perceptions and increase switching rates.
Keywords: C91; D14; D91; G21; G28; G41; 330; financial decision-making; consumer advice; mortgages; switching; behavioural economics